Analisis Sanitasi Bandar Udara Fatmawati Soekarno Bengkulu - Wulan Angraini; Afriyanto Afriyanto; Nopia Wati; Henni Febriawati; Sarkawi Sarkawi; Achmad Faisal Rizal; Diyan Pratiwi (Universitas Faletehan, 2024)
Fatmawati Airport as a place for people entering and exiting from various destinations needs attention in the aspect of creating a healthy environment to protect airport users from the spread of disease and health problems. This research aims to analyse the sanitary conditions at Fatmawati Soekarno Airport Bengkulu and received authorization from the Class III Port Health Office in Bengkulu with permit number 238/SKTMP/KKP-BKL/VIII/2021. This research was descriptive observational. The data collection technique used a direct measurement with an observational list. The results showed that the sanitation conditions at Fatmawati Soekarno Airport Bengkulu scored 6900 (56.21%); thus, it was declared unhealthy. The efforts to implement environmental sanitation obtained a score of 54.21%, the arrangement of facilities and infrastructure 56.44%, the increase in clean and healthy living behaviors 71.42%, the improvement of occupational safety and health 85.33%, the security and order 80%, and the institutional aspect 50.26%. The health conditions of the airport environment, facilities, and the institutional efforts were categorized as not good. However, the efforts to increase clean and healthy living behaviors and to increase security and order were categorized as meeting the requirements since the officers outside the airport was mandatory to use PPE (personal protective equipment).